RESEARCH OF THE STATIONARY FIELD IN THE AREA OF ANTIPRISM - Камаєва, Світлана Олегівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Work is devoted to an exploration of the stationary field in the area of antiprism. For this task several mathematical models were built and comparing of obtained results with the results, obtained by the known discrete methods, was conducted.